Analisis Penggunaan Knalpot Racing Slip-On Dan Knalpot Racing Full System Terhadap Performa Mesin Pada Motor 150 CC - Wibowo, Trio Nur; Prabowo, Nugrah Rekto; Purwanto, Dwi (UM Purwokerto Press, 2023)
One way to improve the performance of an engine without dismantling the original engine is to modify the exhaust pipe, which is commonly called the exhaust. Here we use 4 types of exhaust, namely factory standard exhaust, slip-on exhaust (standard header-modified muffler), slip-on (modified header-standard muffler), and full system exhaust that we take from the market. This study aims to test the performance of the motor which consists of torque, power, and exhaust emissions (CO and HC levels) from the four types of exhausts, using a dynamometer to determine torque and power, an emission gas analyzer to determine the level of exhaust emissions (CO and HC). Our experimental results show the data, the results are still below the standards set by the Indonesian government. The greatest torque of 15.02 N.m at 7500 rpm and the greatest power of 18.36 hp is achieved by a full-system modified exhaust compared to the standard exhaust with the highest torque of 14.62 N.m at 7000 rpm and the highest power of 16.67 hp at 9500 rpm. The best exhaust emission levels are achieved by standard exhaust with the largest CO content of 0.62% at 10000 rpm and the largest HC content of 107 ppm at 10000 rpm compared to full system exhaust with the largest CO content of 1.79% at 10000 rpm and 201 ppm HC levels at 10000 rpm, in other words the standard exhaust is still more environmentally friendly than the full system exhaust.